TRADISI DAN RELIGI SEBAGAI UPAYA KONSERVASI MATA AIR MASYARAKAT PERDESAAN: STUDI KASUS MASYARAKAT KECAMATAN GIRIMULYO, KABUPATEN KULON PROGO (Tradition and religion as means of the rural community in spring conservation: a case study of Girimulyo Distric, Kulon Progo Region) - Sudarmadji Sudarmadji; Fajar Sugiarto; Ratna Destra Kurniasari; Indra Agus Riyanto; Ahmad Cahyadi; Sudrajat Sudrajat (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2017)
Tradition and religion interact closely to the rural community, which is shown in their culture. This concept was applied to spring conservation in the rural area. The objective of this research was to show the role of tradition and religion in the use of spring based conservation by rural community. This research used a case study method. Data were collected by field surveys and interviews. The respondents were chosen randomly because the characteristic of the community was homogenous. The results of this research showed that tradition and religion in form of cultural ritual called spring cleaning (nguras sumber) and “be grateful to God” (slametan) had been capable to keep the sustainability of water resources in the spring, both the quantities and qualities of water. Nguras Sumber and Slametan were directed by a traditional leader called “Juru Kunci” followed by the community. The water resources were used for domestic water consumption, tourism, agriculture, and livestock throughout the year, even excessive in the rainy season. Therefore, the culture of Nguras Sumber and Slametan could be maintained as a form of spring’s conservation.